An Extended GRA Method Integrated with Fuzzy AHP to Construct a Multidimensional Index for Ranking Overall Energy Sustainability Performances - ÇOBANOĞLU, EMİNE; VAYVAY, ÖZALP (MDPI, 2020)
In an age of rapid technological advancement, the increasing need for energy and its related services to satisfy economic and social development has become a critical concern of national governments worldwide. This has triggered researchers to work on metrics for tracking and tracing energy sustainability in order to provide monitoring mechanisms for policy makers. In this regard, multicriteria decision-making (MCDM) methods are becoming more popular to deal with the multidimensional and complex nature of sustainability. We have proposed an extended and revised version of the grey relational analysis (GRA) method, which is integrated with the fuzzy analytic hierarchy process (AHP), to develop a new composite index for comparing the overall energy sustainability performances of 35 OECD member countries. Our case study revealed the performances of selected countries by providing their strengths and weaknesses based on determined criteria as well as the level of change in performances with different criteria weights. The proposed GRA model can be used in different applications of sustainability due to its flexible nature, which provides benefits from goal-oriented extensions in order to adequately capture different aspects of sustainability.
Keywords: overall energy sustainability; multicriteria decision-making; fuzzy analytic hierarchy process; extended grey relational analysis; composite index; OECD member countries; monitoring tool; GREY RELATIONAL ANALYSIS; MULTICRITERIA DECISION-MAKING; ANALYTIC HIERARCHY PROCESS; SUPPLIER SELECTION; INDICATORS; CRITERIA; SYSTEM; SECURITY; VIKOR